Ceramic compositions for 5G devices containing niobium: A survey - Reginaldo Muccillo; Eliana N. S. Muccillo (International Journal of Ceramic Engineering & Science, 2024)
Abstract The main dielectric properties of several ceramic materials having niobium in their composition, proposed to take part in 5G telecommunication devices, are reviewed. A preliminary basic presentation of 5G systems, the requirements for implementing their use, a concise review of the ceramic compositions containing niobium that have been studied thus far, and an evaluation of their performance are detailed. A survey is presented, including more than 80 different compositions containing niobium, focusing on key parameters, such as dielectric constant, quality factor, temperature coefficient, and sintering temperature. These parameters play a role for assessing the potential application of these ceramics in 5G devices.